Production of freeze-dried flaxseed oil powders by using rocket seed gum as an alternative novel encapsulation agent to improve oxidative stability - Avci, Esra; Karadag, Ayse; Karasu, Salih (Universiti Kebangsaan Malaysia, 2022)
Flaxseed oil rich in α-linolenic acid (ALA) has many health beneficial properties, but suffers from oxidation degradation due to its unsaturated nature, and may need a protective delivery system to apply to different food formulations. In this study, the rocket seed gum was used as a novel encapsulation agent to produce freeze-dried powders. The rocket seed gum (RSG), gum arabic (GA), and their combination were used at two different oil: wall material ratios. Replacing GA with RSG changed the flow behavior of emulsions from Newtonian to shear-thinning, also RSG addition improved the rheological properties of flaxseed emulsion and provided viscoelastic solid characteristics. The encapsulation efficiency (EE %) of flaxseed oil was changed between 38.14 and 52.37%. The effect of wall material type was not significant while the ratio of wall material to oil was significant (p<0.05). The FT-IR image of powders showed that flaxseed oil was successfully encapsulated by the RSG. The flaxseed oil powders prepared by RSG showed 3.12 to 5.73 times higher oxidative stability than the flaxseed oil and the powder prepared only with GA. The more amount of air voids observed in SEM images of powders produced with GA might also be related to their lower oxidative stability. Our study showed that rocket seed gum can be successfully used as a new encapsulation agent to produce oxidatively stable microencapsulated flaxseed oil powders.